2014
DOI: 10.1117/12.2046917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EUV resist performance below 20nm CD using helium ion lithography

Abstract: For the introduction of EUV lithography, development of high performance EUV resists is of key importance. This development involves studies into resist sensitivity, resolving power and pattern uniformity. We have used a subnanometer-sized 30 keV helium ion beam to expose chemically amplified (CAR) EUV resists. There are similarities in the response of resists to He + ions and EUV photons: both excite Secondary Electrons with similar energy distributions. The weak backscattering of the He + ions results in ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Our simulation results are in good agreement with experiments reported by Maas et al. 6 Furthermore, we investigate the advantages of optimizedpixel-dose SHIBL to improve LCDU, LWR, exposure latitude (EL) and throughput. Finally, we compare preliminary modeling results for single-pixel and optimized-pixel-dose SHIBL for a 50-nm-full-pitch LS pattern.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Our simulation results are in good agreement with experiments reported by Maas et al. 6 Furthermore, we investigate the advantages of optimizedpixel-dose SHIBL to improve LCDU, LWR, exposure latitude (EL) and throughput. Finally, we compare preliminary modeling results for single-pixel and optimized-pixel-dose SHIBL for a 50-nm-full-pitch LS pattern.…”
Section: Introductionsupporting
confidence: 81%
“…high contrast) 10 due to high sensitivity of CAR to He-ions and spatial resolution. 6 Furthermore, it is worth mentioning that it has been reported that optical critical dimension (OCD) scatterometry provides a more accurate measure of CD, for a valid number of similar features, than CD-SEM metrology. 11-13 Therefore, we translated our CD-SEM metrology data for LS and CH patterns to YieldStar metrology (ASML OCD scatterometrybased metrology) data using first order fit equations provided by ASML (Veldhoven).…”
Section: Point-spread Function For Shibl In Carmentioning
confidence: 99%
See 3 more Smart Citations